Serological prevalence of Brucella spp. at the livestock-human interface in Jordan - Ehab A. Abu-Basha; Zuhair Bani Ismail; Lea Widemann; Yasmin Daradkeh; Omar Al-Omari; Alaa Fahmawi; Mais Lakaideh; Belal Sha'fout; Haia Mellhem; Leen Al-Bayari; Hani Talafha; Zaidoun Hijazeen; et al. (One Health)
Despite its endemic status in the Middle East, key knowledge gaps persist regarding the prevalence, transmission rate, and geographical distribution of both human and livestock brucellosis in Jordan. This study aimed to investigate the seroprevalence of human and livestock brucellosis as well as the incidence of brucellosis in humans in Jordan. A total of 500 human participants (202 exposed and 296 unexposed to livestock) were enrolled in the study. Sampling was conducted at baseline and 1.5 years later. Additionally, a total of 700 livestock were sampled, comprising 20 animals per taxa (camels, cattle, sheep, goats) per site, at both baseline (N = 350) and the 1.5-year follow-up (N = 350). Human participants were longitudinally followed, whereas livestock sampling was conducted opportunistically. Blood samples obtained from both humans and livestock at baseline and follow-up were tested for Brucella spp. serum antibodies using the Rose Bengal test (RBT) and complement fixation test (CFT). The overall seroprevalence of brucellosis in humans at baseline was 3.4 % (95 % CI: 2.0–5.4). Positive test results in humans were detected from all five sites with no significant regional variation observed. Seroprevalence was higher in individuals regularly exposed to livestock (6.1 %; 95 % CI: 3.5–9.9) compared to those not regularly exposed (0.80 %; 95 % CI: 0.10–2.9). Incidence of human brucellosis was 924 seropositives per 100,000 person-years, with all incident seropositives occurring in the livestock-exposed cohort. In livestock, the overall seroprevalence of brucellosis was 5.4 % (95 % CI: 3.5–8.3) at baseline compared to 2.6 % (95 % CI: 1.4–4.8) at follow-up. Seropositive livestock were detected at all sites apart from Al-Zarqa, and in all species apart from camels. In conclusion: Brucellosis burden was higher among humans regularly exposed to livestock, re-emphasizing the need for disease control in livestock populations to prevent primary infection in humans.